STAGES OF GRIEF IN KATHLEEN GLASGOW “HOW TO MAKE FRIENDS WITH THE DARK” - Winardi, Yohanes Kurniawan; Subianto, Audrey Eveline (BASIS (Bahasa dan Sastra Inggris), 2023)
The grieving process, as described in the book "How to Make Friends with the Dark" by Kathleen Glasgow, has been investigated in this study. Following the loss of a loved one, those who grieve go through a natural process of mourning that can be summarized in the phrase "journey of grief." The researcher chose the sixth stage of grief theory from Kübler Ross and David Kessler to analyse the data in this study. This study examines the psychological state of the main character by using the theories of Kübler Ross and David Kessler through the novel "How to Make Friends with the Dark." The results are exploited by offering a detailed list of Tiger's developing relationship with darkness itself. The researcher examines and analyses the book to compile a list of Tiger's speeches as described therein. The six stages of grieving can be seen to correlate with each item on the list. As a result, the main characters in this book go through the stages of grieving in their own unique and distinctive way, which helps them reach the end of their journey—finding meaning. It shows that the main character in the novel experiences all six stages of grief, namely denial, anger, bargaining, depression, acceptance, and finding meaning. Initially, Tiger did not accept her mother's death. However, at the end of the story, she decides to move on and learn to make friends with her darkness.